Newspaper coverage on global climate change: an analysis on Malaysia mainstream newspapers / Nor Jijidiana Azmi - Azmi, Nor Jijidiana (2012)
Global Climate Change can affect human life and activities. The rising amount of natural disasters, the warming of the Earth and the melting of the icebergs are some examples of its effects. Newspapers in developed countries such as the United States, Japan and United Kingdom began to give more coverage on the issue. Studies show that the increasing number of newspapers coverage can significantly contribute to the increasing level of public awareness on the issue. This study is conducted to analyze the coverage of global climate change issue in four Malaysia mainstream newspapers. The data for this study are collected from January 2008 to December 2010. A content analysis is conducted to identify the frequency of the articles related with global climate change, the articles length, the trend of newspaper coverage and the frames of the articles. The frames of the articles which are adopted from Boykoff (2009) study are divided into three subcategories. The subcategories are the cause, the synthesis effects of global climate change and audience reactions towards the issue. The findings for this study will provide an understanding about the ways Malaysia mainstream newspapers provide the coverage about Global Climate Change and the audience reactions towards the issue. In general, the degree of concern and attention on newspaper coverage on global climate change issue in four Malaysia mainstream newspapers are differ. The finding suggested that there is an improvement in the coverage of global climate change issue in Malaysia mainstream newspapers. The findings also suggested that there is a significant relationship between the coverage of global climate change and the events pertaining the issue. Finally, the result on the frames indicates that the most published topic in global climate change issue is public action to reduce the effects of global climate change and reduce the emissions of the greenhouse gas.